Association of vitamin D receptor gene polymorphisms and vitamin D levels with asthma and atopy in Cypriot adolescents: a case–control study - Papadopoulou, Anna; Kouis, Panayiotis; Middleton, Nicos; Kolokotroni, Ourania; Karpathios, Themistokles; Nicolaidou, Polyxeni; Yiallouros, Panayiotis K. (My University, 2015)
Background.Polymorphisms in the vitamin D receptor (VDR) gene have been studied in immune-related disorders either as independent contributors or in combination with vitamin D concentration. Vitamin D and VDR have been independently linked to asthma susceptibility. We investigated whether VDR variants were associated independently or in relation to vitamin D levels with asthma in Cypriot adolescents.Methods. We studied 190 current wheezers, 69 of which were categorized as active asthmatics and 671 healthy controls. We determined three VDR genotypes (BsmI, TaqI, ApaI) and measured serum 25(OH)D levels. Logistic regression and stratified analyses by the presence of hypovitaminosis D (≤20 ng/ml) were used to evaluate the association of the VDR variants with asthma.Results.The distribution of TaqI genotypes was significantly different between controls and current wheezers (p = 0.030) or active asthmatics (p = 0.014). The tt genotype was over-represented in wheezers (19.2 %) and asthmatics (21.3 %) compared to respective controls (12.9 %). No difference was observed between controls, current wheezers and active asthmatics in the genotypic distribution of BsmI and ApaI polymorphic sites. After stratification by the presence of hypovitaminosis D, a significant association was detected between tt genotype of TaqI polymorphism with wheezing (OR: 1.97, 95 % CI: 1.12, 3.46) and asthma (OR: 2.37, 95CI%: 1.02, 5.52) only in those with normal vitamin D levels (>20 ng/ml) but not in subjects with low vitamin D.Conclusions.The minor TaqI genotype of VDR is associated with asthma in Cypriot adolescents. This polymorphism may contribute to asthma susceptibility primarily under conditions of normal vitamin D levels (>20 ng/ml).
Keywords: Vitamin D; VDR; Asthma; Polymorphisms; Adolescents